The interaction between oscillating-grid turbulence and a sediment layer - Wan Mohtar, Wan Hanna Melini (2011)
The critical conditions for incipient sediment motion induced by oscillating-grid generated turbulence interacting with a sloping sediment layer were investigated experimentally. Near-spherical monodisperse sediments were used throughout with relative densities of 1.2 and 2.5 and mean diameters(d)ranging between 80 and 1087 μm. Interaction characteristics were analysed in terms of the critical Shields parameter θc, defined using the peak root mean square (r.m.s) horizontal velocity component in the near-bed region. Bed slope effects on θc were investigated by tilting the bed (and the grid) at angles between 0 and the repose limit. In all cases, the grid was aligned to be parallel to the bed surface, so that the oscillation direction is always normal to bed surface. The measured values of θc on a horizontal bed were comparable to the values reported in the traditional Shields diagram with θc seen to increase monotonically for hydraulically smooth bedforms and to be approximately constant for hydraulically rough bedforms. To account for bed slope effects, the measured values of θc were compared with a force-balance model based on the conditions for incipient grain motion on a sloping bed. For hydraulically smooth bedforms, where the bed roughness is small compared to the boundary-layer depth, the model was derived to account for how viscous stresses act to damp the drag and lift forces acting on the near surface sediment. For hydraulically rough bedforms, where this viscous-damping effect is not present, the model assumes the standard approach with the drag and lift forces scaling with the square of the near-bed (inviscid)velocity scale. In both cases the model predicts the bedforms to become more mobile as the bed slope is increased. However, the damping effect of the viscous sublayer acts as a stabilizing influenced for hydraulically smooth bedforms, to reduce the rate at which the bed mobility increases with bed slope. The measured values of θc in the hydraulically rough bedforms were in agreement with the trends predicted by this model. However, measured θc in smooth bed cases were lower than predicted, and fall on the hydraulically rough trend when bed slope is < 20. When the bed slope reaches the repose limit, θc falls between the smooth-bed and rough-bed cases. Measurements of sediment trajectories due to the turbulence interacting with the bed were obtained, for a range of impact conditions. Observations of the sediment trajectories during the interaction show the individual sediment grains to be predominantly displaced in a circular 'splash'. Data showed that the ‘splash’ feature and particle entrainment within the turbulence structure was within one eddy turnover time.